cGMP-Phosphodiesterase Inhibition Enhances Photic Responses and Synchronization of the Biological Circadian Clock in Rodents - Plano, Santiago A. (Public Library of Science, 2012)
The master circadian clock in mammals is located in the hypothalamic suprachiasmatic nuclei (SCN) and is synchronized by several environmental stimuli, mainly the light-dark (LD) cycle. Light pulses in the late subjective night induce phase advances in locomotor circadian rhythms and the expression of clock genes (such as Per1-2). The mechanism responsible for light-induced phase advances involves the activation of guanylyl cyclase (GC), cGMP and its related protein kinase (PKG). Pharmacological manipulation of cGMP by phosphodiesterase (PDE) inhibition (e.g., sildenafil) increases low-intensity light-induced circadian responses, which could reflect the ability of the cGMP-dependent pathway to directly affect the photic sensitivity of the master circadian clock within the SCN. Indeed, sildenafil is also able to increase the phase-shifting effect of saturating (1200 lux) light pulses leading to phase advances of about 9 hours, as well as in C57 a mouse strain that shows reduced phase advances. In addition, sildenafil was effective in both male and female hamsters, as well as after oral administration. Other PDE inhibitors (such as vardenafil and tadalafil) also increased light-induced phase advances of locomotor activity rhythms and accelerated reentrainment after a phase advance in the LD cycle. Pharmacological inhibition of the main downstream target of cGMP, PKG, blocked light-induced expression of Per1. Our results indicate that the cGMP-dependent pathway can directly modulate the light-induced expression of clock-genes within the SCN and the magnitude of light-induced phase advances of overt rhythms, and provide promising tools to design treatments for human circadian disruptions.